2012
DOI: 10.4103/0019-5413.101043
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of the impact of fibular osteotomies at tibiotalar joint: A cadaveric study

Abstract: Background:Osteotomy of the fibula is a common orthopedic procedure performed for various indications, including harvesting fibula for grafting purposes. The effect of fibular osteotomy and need for tibiofibular syndesmotic fixation fusion at different levels on tibiotalar joint is matter of debate. We performed a biomechanical analysis of the impact of fibular osteotomies at different levels and whether the fixation of distal tibiofibular joint mitigates instability caused by the osteotomy.Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It is important to note that the fibula plays a likely role in tibiotalar contact mechanics even with intact ligaments. 24,31 Yang et al performed suprasyndesmotic fibular osteotomies and found significant reductions in tibiotalar contact area measured using a K-Scan pressure sensor (Tekscan), even though the syndesmotic ligaments (but not the IOM) remained intact. Restoring and fixing the bone and stabilizing the syndesmosis normalized contact area in their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the fibula plays a likely role in tibiotalar contact mechanics even with intact ligaments. 24,31 Yang et al performed suprasyndesmotic fibular osteotomies and found significant reductions in tibiotalar contact area measured using a K-Scan pressure sensor (Tekscan), even though the syndesmotic ligaments (but not the IOM) remained intact. Restoring and fixing the bone and stabilizing the syndesmosis normalized contact area in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Restoring and fixing the bone and stabilizing the syndesmosis normalized contact area in their study. 31 Given the apparent relationship between tibiotalar contact area and the position of the talus and fibula relative to the tibia (linear and rotational), the importance of syndesmotic stability for protecting the joint from injury becomes more evident. Alterations in the magnitude and location of intra-articular pressure found in our study after disruption of the IOL and PITFL could explain both acute and longterm joint conditions.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, there is concern that operative disruption of the syndesmosis may result in morbidity, including rotational instability. 3,6,7,19,22,25 The results from our study demonstrate that the anterolateral tibial osteotomy is a reasonable alternative for accessing lateral or posterior lesions for AOT with limited morbidity associated with the osteotomy, strong evidence of adequate osteotomy healing, and good clinical outcomes.…”
Section: Discussionmentioning
confidence: 59%
“…Reconstruction of the fibula defect after harvesting might not be necessary, because the fibula and interosseous membrane carry only 6% to 16% of the load applied to the lower extremity [10, 11] and spontaneous regeneration of the fibula has been reported previously, especially in children [12]. However, incomplete regeneration or nonunion following fibula harvesting has also been described [1, 13], and the loss of the fibula after its removal sometimes results in significant donor site morbidity, such as surgical scar pain, weaknesses of plantar flexion of the ankle [14], valgus deformity of the ankle [1], ankle instability [15], and tibial fracture [2]. Our case demonstrated slight proximal migration of the remaining distal fibula without ankle valgus deformity, which could be avoided by using temporary syndesmotic screw fixation.…”
Section: Discussionmentioning
confidence: 99%